Implantable device and method for preparing the same
By forming a microporous polymer coating on the wire surface of the implantable instrument, the problem of long endothelialization time and risk of thrombosis in the organism is solved, and rapid endothelialization and safe implantation effect is achieved.
Patent Information
- Application Number
- CN202011602222.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2040-12-29
AI Technical Summary
The cardiac occluder made of existing shape memory alloy materials is difficult to rapidly endothelialize in the organism, resulting in a long sealing time and easy formation of thrombosis, increasing the risk of thromboembolic.
Design an implantable instrument with a support frame consisting of multiple intersecting wires. The surface of the wire is covered with a polymer coating. The coating has multiple micropores, an average pore diameter of 5μm to 500μm and a porosity of 20% to 85. % to promote endothelial cell crawling and rapid endothelialization.
Through the design of microporous polymer coatings, the endothelialization process is significantly accelerated, the risks of thrombosis and shedding are reduced, and the safety and stability of the device are improved.
Smart Images

Figure CN114680950B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of interventional medical devices, and in particular to an implantable device and a preparation method thereof. Background Art
[0002] This section merely provides background information related to the present disclosure and is not necessarily prior art.
[0003] Percutaneous interventional therapy is a rapidly developing disease treatment method in recent years, and the application areas of this therapy are becoming more and more extensive. Among them, the use of transcatheter interventional therapy can place devices and / or drugs into the heart, arteries and veins of the human body. Among them, the device can be a heart occluder, a vascular occluder, a vascular filter, a vascular stent, etc.
[0004] Traditional cardiac occluders or vascular occluders are generally made of shape memory alloys, which can return to their original shape after release and fit the defective tissue well. However, the current shape memory alloy materials are generally non-corrosive or non-degradable in the body. After endothelialization is completed and complete occlusion is achieved, the occluder made of shape memory alloy materials will remain in the body permanently, which may pose long-term clinical risks.
[0005] Occluders or other implantable devices made of absorbable polymer materials can be degraded in the body, so that the occluder can be gradually degraded and the degradation products are absorbed by the body without residue in the body, thus avoiding long-term clinical risks. However, absorbable polymer materials, such as polylactic acid, have a tight molecular chain structure, which makes it take a long time for biological tissues and occluders to penetrate each other, and the endothelialization time is long. In this way, not only does it take a long time to achieve complete occlusion, but it is also easy to form thrombi on the surface of the device, and the formed thrombi may fall off the device and cause thromboembolism and other problems. Summary of the invention
[0006] Based on this, it is necessary to provide an implantable device that can achieve endothelialization more quickly.
[0007] An implantable device comprises a support frame, wherein the support frame comprises a plurality of mutually intersecting silk threads, the surface of the silk threads is provided with a polymer coating, the polymer coating has a plurality of micropores, the average pore size of the plurality of micropores is 5 μm to 500 μm, and the porosity of the polymer coating is 20% to 85%.
[0008] In one embodiment, the support frame includes a first plugging unit, a second plugging unit, a waist, a first head and a second head, the two ends of the waist are respectively connected to the first plugging unit and the second plugging unit, the first head is arranged at the end of the first plugging unit away from the waist, and the second head is arranged at the end of the second plugging unit away from the waist, a polymer coating is arranged on the surface of one of the first head and the second head, the polymer coating has a plurality of micropores, the average pore size of the plurality of micropores is 5μm to 500μm, and the porosity of the polymer coating is 20% to 85%.
[0009] In one embodiment, the support frame includes a first sealing unit, a second sealing unit, a waist, a first head and a second head, the two ends of the waist are respectively connected to the first sealing unit and the second sealing unit, the first head is arranged at an end of the first sealing disk away from the waist, the second head is arranged at an end of the second sealing unit away from the waist, and at least one of the first head and the second head has a hole.
[0010] In one embodiment, when the first head has holes, the average pore size of the holes of the first head is 5μm to 200μm, and the porosity is 30% to 40%; when the second head has holes, the average pore size of the holes of the second head is 5μm to 200μm, and the porosity is 20% to 30%.
[0011] In one embodiment, the pores are filled with a soluble substance.
[0012] A method for preparing an implantable device comprises the following steps:
[0013] providing a support frame, the support frame comprising a plurality of mutually intersecting wires;
[0014] Dissolving a polymer in a first solvent to obtain a mixed solution, and adding a second solvent to the mixed solution to obtain a mixture;
[0015] immersing the support frame in the mixture;
[0016] After taking the support frame out of the mixture, cooling it to the gel point temperature of the polymer and roughening it at the gel point temperature;
[0017] The roughened support frame is cooled and then freeze-dried under vacuum to form a polymer coating on the multiple wires of the support frame. The polymer coating has multiple micropores with an average pore size of 5μm to 500μm and a porosity of 20% to 85%.
[0018] In one embodiment, the volume of the second solvent accounts for 1-15% of the volume of the mixed solution, and the mass of the polymer accounts for 3%-30% of the volume of the first solvent, wherein the mass of the polymer is expressed in milligrams and the volume of the first solvent is expressed in milliliters.
[0019] In one of the embodiments, in the step of immersing the support frame in the mixture, the immersion time is 1 to 20 minutes.
[0020] In one embodiment, the roughening time is 1 to 60 minutes.
[0021] A method for preparing an implantable device comprises the following steps:
[0022] providing a support frame, the support frame comprising a plurality of mutually intersecting wires;
[0023] dissolving the polymer and the soluble substance in a first solvent to obtain a mixture;
[0024] immersing the support frame in the mixture;
[0025] removing the support frame from the mixture and drying it to form a polymer film on the surface of the filaments;
[0026] The support frame is contacted with a second solvent to dissolve at least a portion of the soluble substance while the polymer is not dissolved, thereby forming a polymer coating having a plurality of micropores with an average pore size of 30 μm to 500 μm and a porosity of 20% to 85%.
[0027] In the above implantable device, the silk thread of the support frame has a polymer coating with micropores, the average pore size of the micropores is 5μm to 500μm, and the porosity of the polymer coating is 20% to 85%, which is conducive to endothelial cells crawling on the silk thread, thereby facilitating faster endothelialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a structural schematic diagram of an occluder according to an embodiment;
[0029] Figure 2 is a schematic cross-sectional view of a first end cover of an embodiment;
[0030] Figure 3 is a schematic cross-sectional view of a second end cap of an embodiment;
[0031] Figure 4 A top view of an embodiment of the invention in which the distal end of the wire is received in the first sealing head and before hot melting;
[0032] Figure 5 A top view of a proximal end of a wire of an embodiment of the present invention is received in a second end cap and before hot melting;
[0033] Figure 6 A schematic diagram of a state in which the locking piece of the occluder of another embodiment is not connected to the second end cap;
[0034] Figure 7 for Figure 6 A schematic diagram showing a state in which the locking piece of the occluder is connected to the second end cap;
[0035] Figure 8 is a schematic longitudinal section diagram of a first end cover of an embodiment;
[0036] Fig. 9 is a schematic longitudinal section diagram of a second end cover of an embodiment;
[0037] Fig.10 is a schematic longitudinal cross-sectional view of a silk thread according to an embodiment;
[0038] Fig.11 is a flow chart of a method for preparing an implantable device according to an embodiment;
[0039] Fig.12 The present invention is a flow chart of a method for preparing an implantable device according to another embodiment. DETAILED DESCRIPTION
[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0042] In the field of interventional medical devices, the “distal end” is defined as the end away from the operator during surgery, and the “proximal end” is defined as the end close to the operator during surgery. “Axial” refers to the direction parallel to the line connecting the distal and proximal centers of the medical device, and “radial” refers to the direction perpendicular to the axial direction. “Circumferential” refers to the circumferential direction, that is, the direction of the axis around the lumen device.
[0043] An implantable device capable of achieving endothelialization relatively quickly is provided, which is beneficial to avoid thrombus formation on the surface of the implantable device and embolism. The following takes an occluder as an example to explain the implantable device.
[0044] See also Figure 1 , an occluder 100 according to one embodiment includes a support frame 20. The support frame 20 is a mesh structure formed by a plurality of wires 220 intersecting each other. The material of the wires 220 may be a non-degradable metal, for example, the wires 220 may be a nickel-titanium alloy wire, a cobalt-chromium alloy wire or a stainless steel wire. Alternatively, the material of the wires 220 may also be a biodegradable material. For example, the biodegradable material may be at least one of polyracemic lactic acid (PDLLA), poly D-lactic acid (PDLA), poly L-lactic acid (PLLA), polyglycolic acid (PGA), polylactic acid-glycolic acid copolymer (PLGA), polyhydroxyalkanoic acid ester (PHA), polydioxanone (PDO) and polycaprolactone (PCL).
[0045] In this embodiment, the support frame 20 includes a first blocking unit 22, a second blocking unit 24 and a waist 26. The two ends of the waist 26 are respectively connected to the first blocking unit 22 and the second blocking unit 24, forming a two-plate and one-waist structure with large ends and a small middle. The first blocking unit 22, the second blocking unit 24 and the waist 26 are an integrated structure.
[0046] It is understood that in other embodiments, the structure of the support frame 20 is not limited to a two-plate and one-waist structure with large ends and a small middle. For example, when one of the first blocking unit 22 and the second blocking unit 24 is omitted, the first blocking unit 22 or the second blocking unit 24 is connected to the waist 26 to form a support frame 20 with a substantially T-shaped cross section.
[0047] Each wire 220 has two free ends. Figure 1 The occluder 100 further includes a first end cap 40 disposed on the first occluding unit 22 and a second end cap 60 disposed on the second occluding unit 24. The first end cap 40 and the second end cap 60 are both used to converge and fix the wire 220. Specifically, the first end cap 40 is used to fix the distal free end of the wire, and the second end cap 60 is used to fix the proximal free end of the wire 220. In addition, in one embodiment, a movable connection assembly ( Figure 1 The movable connection component is used to be movably connected with the delivery system, so that after the occluder 100 is delivered to the lesion site, the connection with the occluder 100 can be disconnected to release the occluder 100. For example, the movable connection component can be a thread, a plurality of strands of wire, etc., provided on the second end cap 60, so that the second end cap 60 can be movably connected with the delivery system.
[0048] In one embodiment, the first end cap 40 and the second end cap 60 are both hollow cylindrical structures. Figure 2 As shown, the first end cap 40 has a receiving cavity 41 inside. Figure 3 As shown, the second end cap 60 has a receiving cavity 61 inside, and the two ends of the wire 220 are respectively received and fixed in the receiving cavity 41 of the first end cap 40 and the receiving cavity 61 of the second end cap 60. In one embodiment, the wire is fixedly connected to the first end cap 40 and the second end cap 60 by hot melting.
[0049] At least one of the first head 40 and the second head 60 has a hole.
[0050] Please continue reading Figure 2 In one embodiment, the first end cap 40 is a hole structure, that is, the first end cap 40 has a plurality of holes 42. Moreover, the holes 42 extend from the surface of the first end cap 40 to the first end cap 40. The holes 42 do not penetrate the first end cap 40 to maintain the structural integrity of the first end cap 40. That is, the opening end of the hole 42 is located on the surface of the first end cap 40.
[0051] In one embodiment, all holes 42 on the first end cap 40 extend from the outer surface of the first end cap 40 to the inside of the first end cap 40 (towards the direction of the receiving cavity 41 close to the first end cap 40), and the holes 42 do not penetrate the first end cap 40. That is, the first end cap 40 does not have holes 42 extending from the inner surface of the first end cap 40 to the outside of the first end cap 40 (towards the direction of the receiving cavity 41 away from the first end cap 40). When the occluder 100 is implanted in a biological body, generally, endothelial cells first crawl along the outer surface of the occluder 100 to form an endothelial cell membrane covering the occluder 100. The holes 42 extending from the outer surface to the inside of the first end cap 40 are provided on the first end cap 40, which is conducive to the crawling of endothelial cells. In addition, the first end cap 40 does not have holes 42 extending from the inner surface of the first end cap 40 to the outside of the first end cap 40, so that the first end cap 40 has sufficient strength.
[0052] like Figure 3 As shown, in one embodiment, the second end cap 60 is a hole structure, that is, the second end cap 60 has a plurality of holes 62. In addition, the holes 62 extend from the surface of the second end cap 60 to the second end cap 60. The holes 62 do not penetrate the second end cap 60 to maintain the structural integrity of the second end cap 60. That is, the opening end of the hole 62 is located on the surface of the second end cap 60.
[0053] In one embodiment, all holes 62 on the second end cap 60 extend from the outer surface of the second end cap 60 to the inside of the second end cap 60 (towards the direction of the receiving cavity 61 close to the second end cap 60), and the holes 62 do not penetrate the second end cap 60. That is, the second end cap 60 does not have holes 62 extending from the inner surface of the second end cap 60 to the outside of the second end cap 60 (towards the direction of the receiving cavity 61 away from the second end cap 60). The second end cap 60 is provided with holes 62 extending from the outer surface to the inside of the second end cap 60, which is conducive to the endothelial cell crawling. In addition, the second end cap 60 does not have holes 62 extending from the inner surface of the second end cap 60 to the outside of the second end cap 60, so that the second end cap 60 has sufficient strength.
[0054] The first head 40 has a plurality of holes 42 and / or the second head 60 has a plurality of holes 62. When the occluder 100 is implanted in the body, the holes 42 facilitate endothelial cells to crawl on the surface of the first head 40, and the holes 62 facilitate endothelial cells to crawl on the surface of the second head 60, thereby achieving endothelialization more quickly.
[0055] See also Figure 4 In one embodiment, the first end cap 40 includes a first outer sleeve 43 and a first inner sleeve 45. The first inner sleeve 45 is received in the first outer sleeve 43, and a gap is formed between the first inner sleeve 45 and the first outer sleeve 43. Figure 5 The second end cap 60 includes a second outer sleeve 63 and a second inner sleeve 65. The second inner sleeve 65 is received in the second outer sleeve 63, and a gap is formed between the second inner sleeve 65 and the second outer sleeve 63. The distal ends 221 of the plurality of wires 220 are received in the gap between the first inner sleeve 45 and the first outer sleeve 43, and the proximal ends 222 of the plurality of wires 220 are received in the gap between the second inner sleeve 65 and the second outer sleeve 63. After hot melting, the distal ends 221 of the wires 220 are melted into one with the first inner sleeve 45 and the first outer sleeve 43, and the proximal ends 222 of the wires 220 are melted into one with the second inner sleeve 65 and the second outer sleeve 63.
[0056] In this way, the connection between the first end cap 40 and the wire 220 and the connection between the second end cap 60 and the wire 220 are more reliable. In addition, the hole 42 on the first end cap 40 extends from the outer surface of the first outer sleeve 43 to the inside of the first outer sleeve 43, and the hole 42 does not penetrate the first outer sleeve 43. The hole 62 on the second end cap 60 extends from the outer surface of the second outer sleeve 63 to the inside of the second outer sleeve 63, and the hole 62 does not penetrate the second outer sleeve 63. In this way, the first end cap 40 and the second end cap 60 have the effect of promoting endothelial cell climbing, and the hole 42 and the hole 62 have little effect on the strength of the first end cap 40 and the second end cap 60, respectively.
[0057] When the number of holes 42 on the first end cap 40 is large, it is beneficial for endothelial cells to crawl on the first end cap 40. Similarly, when the number of holes 62 on the second end cap 60 is large, it is beneficial for endothelial cells to crawl on the second end cap 60. However, when the number of holes 42 is too large, the porosity of the first end cap 40 is too large, resulting in a weak connection between the first end cap 40 and the thread 220, and the thread 220 is easy to fall off from the first end cap 40. When the number of holes 62 is too large, the second end cap 60 has too many holes, resulting in a weak connection between the second end cap 60 and the thread 220, and the thread is easy to fall off from the second end cap 60.
[0058] Therefore, in one embodiment, the average pore size of the plurality of holes 42 of the first end cap 40 is 5 μm to 200 μm, and the porosity of the first end cap 40 is 30% to 40%, so as to take into account both the endothelial creeping and the connection strength between the first end cap 40 and the wire 220. In one embodiment, the average pore size of the plurality of holes 62 of the second end cap 60 is 5 μm to 200 μm, and the porosity of the second end cap 60 is 30% to 40%, so as to take into account both the endothelial creeping and the connection strength between the second end cap 60 and the wire 220.
[0059] It should be noted that the porosity refers to the percentage of the opening area of the hole on the head surface to the surface area of the head. For example, when the first head 40 is a hollow cylinder, the porosity of the first head 40 refers to the percentage of the opening area of the hole 42 on the side of the cylinder to the area of the side of the cylinder. When the second head 60 is a hollow cylinder, the porosity of the second head 60 refers to the percentage of the opening area of the hole 62 on the side of the cylinder to the area of the side of the cylinder. The area of the side of the first head 40 and the second head 60 can be obtained by calculation, and the opening area of the hole 42 and the opening area of the hole 62 can be measured by a microscope.
[0060] In one embodiment, the first head 40 has a hole 42 and the second head 60 has a hole 62, which facilitates the endothelial cells to crawl on the first head 40 and the second head 60, so that the first head 40 and the second head 60 are covered by the endothelial cell membrane more quickly.
[0061] Since the second end cap 60 is connected to the conveying system during the conveying process, the second end cap 60 should have sufficient mechanical strength to ensure the reliability of the connection. Therefore, in one embodiment, the porosity of the second end cap 60 is smaller than that of the first end cap 40, so that the first end cap 40 itself has a better endothelialization promoting effect, and the endothelialization promoting effect and mechanical strength of the second end cap 60 itself are taken into account.
[0062] In one embodiment, if Figure 6 and Figure 7As shown, the occluder 100 also includes a locking member 80. The locking member 80 extends axially in the support frame 20, and one end of the locking member 80 is fixedly connected to the first end cap 40, and the other end is detachably connected to the second end cap 60. When the locking member 80 is connected to the second end cap 60, the axial distance between the first plugging unit 22 and the second plugging unit 24 of the support frame 20 is fixed, so that the occluder 100 can reliably plug the defective part. Therefore, the second end cap 60 is not only connected to the conveying system, but also serves as an element that carries the locking member 80. When the locking member 80 is connected to the second end cap 60, the second plugging head 60 is subjected to the continuous force of the locking member 80. In order to ensure the reliable connection between the locking member 80 and the second end cap 60, the second end cap 60 should have sufficient strength. Therefore, in one embodiment, the porosity of the second end cap 60 is 30% to 40%, so as to take into account the effect of endothelial cell crawling and reliable connection with the locking member 80 and the conveying device.
[0063] In one embodiment, the material of the first end cap 40 and the second end cap 60 is a degradable polymer. In one embodiment, the material of the first end cap 40 and the second end cap 60 is selected from at least one of poly(d-lactic acid) (PDLLA), poly(D-lactic acid) (PDLA), poly(L-lactic acid) (PLLA), poly(glycolic acid) (PGA), poly(lactic acid-co-glycolic acid) (PLGA), poly(hydroxyalkanoate) (PHA), polydioxanone (PDO) and polycaprolactone (PCL).
[0064] The materials of the first end cap 40 and the second end cap 60 may be the same or different.
[0065] The materials of the first seal 40 , the second seal 60 , and the wire 220 may be the same or different.
[0066] In one embodiment, at least one of the first seal 40 and the second seal 60 is filled with a soluble substance. For example, the holes 42 on the first seal 40 are filled with a soluble substance, and the holes 62 on the second seal 60 are filled with a soluble substance.
[0067] The soluble substance can be dissolved in media such as blood, physiological saline, water, organic solvents, inorganic solvents, etc. When the occluder 100 is implanted in the body, the soluble substance dissolves to present a pore structure, thereby achieving the effect of promoting endothelial cell attachment.
[0068] The soluble substance is made of a different material from the first and second end caps 40 and 60 and should have different solubility characteristics, so that in a specific solvent, such as water, blood, etc., the soluble substance can be dissolved while the first and second end caps 40 and 60 cannot be dissolved.
[0069] In one embodiment, the soluble substance is a water-soluble material, for example, the soluble substance is at least one of sodium chloride, polyvinyl alcohol, gelatin, polyvinyl pyrrolidone or polyethylene glycol.
[0070] In one embodiment, the soluble substance is a functional substance, for example, including but not limited to, a polypeptide, a protein, a drug, etc.
[0071] In one embodiment, the soluble substance is a substance that can be developed. The substance that can be developed is filled in the hole 42 of the first head 40 and / or the hole 62 of the second head 60, so that during the implantation process, the substance that can be developed can indicate the shape and position of the occluder 100, so that the implantation proceeds smoothly. Therefore, the occluder 100 does not need to be additionally provided with a metal marker to indicate the shape and position of the occluder 100, and can be completely degraded to avoid the metal marker remaining in the body.
[0072] In one embodiment, the hole 42 is omitted. Figure 8 As shown, a polymer coating 46 is disposed on the first sealing head 40, and the polymer coating 46 has a plurality of micropores 462. The average pore size of the plurality of micropores 462 is 5 μm to 500 μm, and the porosity of the polymer coating 46 is 20% to 85%.
[0073] In one embodiment, the hole 62 is omitted. Fig. 9 As shown, a polymer coating 66 is disposed on the second end cap 60, and the polymer coating 66 has a plurality of micropores 662. The average pore size of the plurality of micropores 662 is 30 μm to 500 μm, and the porosity of the polymer coating 66 is 20% to 85%.
[0074] See also Fig.10 A polymer coating 223 is disposed on the surface of the wire 220 . The polymer coating 223 has a plurality of micropores 2232 . The average pore size of the plurality of micropores 2232 is 5 μm to 500 μm. The porosity of the polymer coating 223 is 20% to 85%.
[0075] The porous structure of the polymer coating 223 is conducive to the endothelial cells crawling on the support frame 20, thereby facilitating faster endothelialization and preventing the formation of thrombus on the surface of the support frame 20.
[0076] Furthermore, the polymer coating 223 is attached to the surface of the thread 220 without affecting the strength of the thread 220 itself, so that the support frame 20 has sufficient mechanical properties and can be reliably attached to the defect site before complete endothelialization.
[0077] It should be noted that the porosity of the polymer coating 223 refers to the percentage of the opening area of the micropores 2232 on the outer surface of the polymer coating 223 to the outer surface area of the polymer coating 223. The opening area of the micropores 2232 can be obtained by calculation, and the area of the outer surface of the polymer coating 223 is the area of the outer surface of the wire 220. The area of the outer surface of the wire 220 is calculated based on the length and wire diameter of the wire.
[0078] The porosity of polymer coating 46 and polymer coating 66 is calculated in the same manner as above.
[0079] The porous structure of the polymer coating 46 is provided to facilitate endothelial cells to crawl on the first end cap 40. The porous structure of the polymer coating 66 is provided to facilitate endothelial cells to crawl on the second end cap 60. The endothelial cell membrane connects the first end cap 40 and the support frame 20 as a whole, which is conducive to preventing the first end cap 40 from falling off. The endothelial cells connect the second end cap 60 and the support frame 20 as a whole, which is conducive to preventing the second end cap 60 from falling off. Thus, the safety of use is improved.
[0080] In one embodiment, the hole 42 of the first end cap 40 is filled with a developable substance, the second end cap 60 is filled with a developable substance, and the micropores 2232 of the polymer coating 223 are filled with a developable substance, and the surface of the polymer coating 223 is attached with a developable substance. These developable substances can be dissolved in the blood. During the implantation process, the developable substance can indicate the shape and position of the occluder 100. Therefore, there is no need to set up an additional non-degradable metal marker, so that the occluder 100 can be completely degraded.
[0081] See also Fig.11 , a method for preparing an implantable device according to an embodiment of the present invention comprises the following steps:
[0082] Step 110: Provide a support frame, wherein the support frame includes a plurality of wires intersecting each other.
[0083] In one embodiment, a plurality of silk threads are cross-woven to form a tubular cavity frame with two ends open. The tubular cavity frame is fixed with a first sealing head and a second sealing head, and then shaped to obtain a support frame.
[0084] In one embodiment, the first closure and the second closure are polymer sleeves.
[0085] In one embodiment, one of the first end cap and the second end cap has a hole. In one embodiment, the first end cap with a hole and the second end cap with a hole are prepared by the following method:
[0086] The main material and the soluble substance are uniformly mixed to obtain a mixture, and a solid mixture is prepared by hot melting or solvent mixing, and then a sleeve is prepared by extrusion, spinning, or 3D printing;
[0087] The sleeve is contacted with a solvent, and the solvent dissolves the soluble substances therein but does not dissolve the main material, thereby forming holes on the sleeve to obtain a first end cap or a second end cap.
[0088] Alternatively, a sleeve containing a soluble substance is prepared, and two sleeves are fixed to the two ends of the frame respectively, and the two open ends of the frame are closed and shaped to form a support frame. Then, a solvent that can dissolve the soluble substance but cannot dissolve the main material is used to dissolve the soluble substance to form holes on the sleeve.
[0089] In one embodiment, when it is desired that the pores extend only from the outer surface of the sleeve to the inner surface of the sleeve, the inner surface of the sleeve should be prevented from contacting with the solvent to prevent the soluble material particles near the inner surface from being dissolved by the solvent. For example, the outer surface of the sleeve is repeatedly wiped with a solvent to prevent the inner surface from contacting with the solvent. Alternatively, after protecting the inner surface (inserting a protective plug into the inner cavity of the sleeve to shield the inner surface), the sleeve is immersed in the solvent.
[0090] In one embodiment, a support frame may be formed by 3D printing, in which the threads are connected to each other as an integrated structure, which is different from a support frame formed by weaving, in which the connection relationship or position relationship between the threads is overlapping.
[0091] It can be understood that in one embodiment, when the implantable device is a tubular cavity stent, a tubular cavity frame with two ends opened can be prepared, and the two ends of the tubular cavity frame are closed and sealed with sleeves.
[0092] In one embodiment, after the frame is prepared, it is shaped by heat setting. In one embodiment, the frame is heat treated at 87-93° C. for 9-16 minutes to shape the frame into a supporting frame.
[0093] Step 120: dissolving the polymer in a first solvent to obtain a mixed solution, and adding a second solvent to the mixed solution to obtain a mixture.
[0094] In one embodiment, the polymer is selected from at least one of poly L-lactic acid (PLLA), poly racemic lactic acid (PDLLA), poly D-lactic acid (PDLA), polyglycolic acid (PGA), polylactic acid-glycolic acid copolymer (PLGA), polyhydroxyalkanoate (PHA), polydioxanone (PDO) and polycaprolactone (PCL).
[0095] At the same temperature, the solubility of the polymer in the first solvent is greater, the solubility of the polymer in the second solvent is less, or the polymer is insoluble in the second solvent. In addition, the first solvent and the second solvent are immiscible. In one embodiment, the first solvent is an organic solvent, and the second solvent is an inorganic solvent.
[0096] In one embodiment, the first solvent is selected from at least one of 1,4-dioxane, chloroform, tetrahydrofuran, ethyl acetate, acetonitrile, m-cresol, o-chlorobenzene, nitrobenzene, trichloroacetic acid, isoamyl acetate, toluene, amyl acetate, trichloroethylene, hexafluoroisopropanol, dichloromethane, phenol, tetrachloroethane, dichloromethane and acetone. The second solvent is water.
[0097] It should be noted that in other embodiments, the first solvent is not limited to the types listed above, and any solvent that can dissolve the polymer is applicable. The second solvent is not limited to water, and the solvents used to form the separated polymer-rich phase and solvent-rich phase in the subsequent steps are used.
[0098] In one embodiment, the first solvent is a mixed solvent including an organic solvent and water, and the volume ratio of the organic solvent to water is 95:5 to 80:20.
[0099] When the concentration of the polymer is too high, the resulting polymer coating is denser, which is not conducive to endothelialization. When the concentration of the polymer is too low, it is difficult to form a coating. Therefore, in one embodiment, the mass of the polymer accounts for 3% to 20% of the volume of the first solvent. The unit of the mass of the polymer is milligrams, and the unit of the first solvent is milliliters, that is, the mass value of the polymer measured in milligrams accounts for 3% to 20% of the mass value of the first solvent measured in milliliters.
[0100] In one embodiment, a polymer is dissolved in a first solvent and heated to a temperature above the cloud point of the polymer, and stirred at a constant temperature to promote the dissolution of the polymer. Then, a second solvent is added and stirred at a constant temperature above the cloud point to obtain a mixture.
[0101] Step 130: Soak the support frame in the mixture.
[0102] In one embodiment, the support frame is immersed in the mixture so that the polymer in the mixture adheres to the surface of the wire. During the immersion process, the temperature of the mixture is always maintained above the cloud point temperature of the polymer.
[0103] In one embodiment, the supporting frame is immersed in the mixture for 1 to 20 minutes to fully soak the mixture.
[0104] In one embodiment, before immersing the support frame in the mixture, the step of surface treating the support frame is also included to make it easier for the polymer to adhere to the surface of the silk thread, so that the subsequently formed polymer coating is more firmly bonded to the silk thread.
[0105] In one embodiment, the support frame is surface treated by plasma treatment.
[0106] Step 140: After the support frame is taken out from the mixture, it is cooled to the gel point temperature of the polymer and roughened at the gel point temperature.
[0107] The support frame is slowly and vertically pulled out of the liquid surface, a liquid film is formed on the surface of the silk thread, and the polymer is attached to the surface of the silk thread. Further, the support frame formed with the liquid film is cooled to the gel point temperature of the polymer, and the roughening is performed at the gel point temperature.
[0108] Roughening gradually clarifies the boundary between the polymer-rich phase and the solvent-rich phase, which is conducive to forming sufficiently large micropores in the polymer coating formed subsequently. If the roughening time is too long, the pore size of the micropores of the obtained polymer coating is larger. If the roughening time is short, the pore size of the micropores of the obtained polymer coating is smaller. In one embodiment, in order to obtain a suitable pore size to promote the effect of endothelial cell crawling, the roughening time ranges from 1 to 60 minutes.
[0109] Step 150: Cool the roughened support frame and then freeze-dry it under vacuum to form a polymer coating on the multiple wires of the support frame. The polymer coating has multiple micropores, the average pore size of the multiple micropores is 5μm to 500μm, and the porosity of the polymer coating is 20% to 85%.
[0110] In one embodiment, the roughened support frame is cooled in liquid nitrogen for 1 to 2 hours and then freeze-dried. Due to the different crystallization temperatures of different components of the liquid film during the low-temperature cooling process, the mixed solvent (mixture of the first solvent and the second solvent) will undergo phase separation to obtain a polymer-rich phase and a solvent-rich solid phase. During the freeze-drying process under vacuum, the solvent-rich phase sublimates, thereby releasing the space occupied by the solvent and obtaining a porous structure, i.e., a porous polymer coating.
[0111] In the obtained polymer coating, the average pore diameter of multiple micropores is 5μm-500μm, and the porosity of the polymer coating is 20%-85%.
[0112] It is understood that when the roughened support frame is cooled, it is not limited to cooling in liquid nitrogen, but can also be cooled in an environment where the temperature meets the requirements. The cooling temperature is also not limited to -196°C, but can be any temperature that can achieve phase separation.
[0113] See also Fig.12, a method for preparing an implantable device according to another embodiment comprises the following steps:
[0114] Step 210: Provide a support frame, wherein the support frame includes a plurality of wires intersecting each other.
[0115] The preparation method step 110 of the support frame will not be described in detail here.
[0116] Step 220: dissolving the polymer and the soluble substance in the first solvent to obtain a mixture.
[0117] In one embodiment, the polymer is selected from at least one of poly L-lactic acid (PLLA), poly racemic lactic acid (PDLLA), poly D-lactic acid (PDLA), polyglycolic acid (PGA), polylactic acid-glycolic acid copolymer (PLGA), polyhydroxyalkanoate (PHA), polydioxanone (PDO) and polycaprolactone (PCL).
[0118] If the selected polymer and soluble substance can be dissolved in the same solvent, the polymer and the soluble substance are dissolved in the same solvent, that is, the first solvent is a single solvent.
[0119] If the solubility of the selected polymer and the soluble substance in the same solvent is greatly different, the polymer is dissolved in one solvent to obtain a first solution, the soluble substance is dissolved in another solvent to obtain a second solution, and the first solution and the second solution are mixed. Alternatively, the polymer and the soluble substance are added to a mixed solvent of two solvents at the same time, and the polymer and the soluble substance are fully stirred to dissolve. In this case, the first solvent is a mixed solvent of two solvents.
[0120] In one embodiment, the average particle size of the soluble substance is 3-250 micrometers, so that the average pore size of the prepared silk thread is 5-500 micrometers.
[0121] In one embodiment, the polymer and the soluble substance are dissolved in a first solvent, heated to a temperature above the cloud point temperature of the polymer, and stirred at a constant temperature at the cloud point temperature of the polymer to promote the dissolution of the polymer and the soluble substance.
[0122] In one embodiment, the mass ratio of the soluble substance to the polymer is at least 30%, so that the porosity of the subsequently formed polymer coating is at least 30%.
[0123] Step 230: Soak the support frame in the mixture.
[0124] In one embodiment, the supporting frame is immersed in the mixture for 1 to 20 minutes to fully soak the mixture.
[0125] In one embodiment, before immersing the support frame in the mixture, the step of surface treating the support frame is also included to make it easier for the polymer to adhere to the surface of the silk thread, so that the subsequently formed polymer coating is more firmly bonded to the silk thread.
[0126] In one embodiment, the support frame is surface treated by plasma treatment.
[0127] Step 240: The support frame is removed from the mixture and dried to form a polymer film on the surface of the wire.
[0128] The support frame is slowly and vertically pulled out of the liquid surface, and a liquid film is formed on the surface of the silk thread. The liquid film is a polymer film, and the polymer film contains soluble substances.
[0129] Step 250: contact the support frame with a second solvent to dissolve at least part of the soluble substance while the polymer does not dissolve, and form a polymer coating after drying. The polymer coating has a plurality of micropores, and the average pore size of the plurality of micropores is 5 μm to 500 μm. The porosity of the polymer coating is 20% to 85%.
[0130] The second solvent can dissolve the soluble substances but cannot dissolve the polymer, or the polymer is almost insoluble in the second solvent.
[0131] In one embodiment, the support frame is immersed in a second solvent to dissolve the soluble substance, thereby forming micropores on the polymer film, and a porous polymer coating is formed after drying, wherein the average pore size of the plurality of micropores is 5 μm to 500 μm, and the porosity of the polymer coating is 20% to 85%.
[0132] The preparation methods of the above two implantable devices are simple and easy to control, and can form a porous polymer coating on the surface of the support frame, which is conducive to accelerating the endothelialization process. In addition, this method forms micropores on the polymer coating instead of on the silk thread, which will not destroy the structure of the silk thread itself, and thus does not sacrifice the mechanical properties of the support frame.
[0133] In one embodiment, no matter which method is used to prepare the porous polymer coating attached to the surface of the wire, after the preparation is completed, it also includes the steps of immersing the entire support frame, the first head and the second head in a solution containing the functional substance, then taking it out, and then drying it, so that the functional substance is deposited on the surface of the wire and in the holes of the first head and / or the second head, thereby introducing the functional substance onto the occluder.
[0134] In one embodiment, the functional substance is a substance with a developing function, so that the occluder has a developing function, and no additional metal marker is required, and the shape and position of the occluder can be indicated during the implantation process. Substances with a developing function, such as iohexol, iopamidol, and diatrizoate, are water-soluble substances. After implantation, under the continuous impact of blood, the substance with a developing function is continuously dissolved and metabolized by the body, and will not remain permanently in the body, making the occluder a 100% degradable device.
[0135] It should be noted that the above text uses the occluder as an example to explain the implantable device, but the implantable device is not limited to the occluder, for example, it can be a luminal stent, including but not limited to aortic stents, coronary stents, etc.
[0136] The invention is further described below through more specific embodiments.
[0137] Example 1
[0138] A group of 20 poly-L-lactic acid threads with a wire diameter of 0.40 mm and arranged in parallel and spaced apart are used as longitude threads and a group of 20 poly-L-lactic acid threads with a wire diameter of 0.40 mm and arranged in parallel and spaced apart are used as latitude threads. The longitude threads and latitude threads are cross-woven up and down to form a tubular structure with open ends. After the poly-L-lactic acid powder and sodium chloride (average particle size of 50 microns) are mixed uniformly at a mass ratio of 85:15, they are hot-melted at 200°C for 20 minutes, and a solid mixture is obtained after cooling. The solid mixture is processed into a sleeve, and the two sleeves are fixed to the threads at both ends of the frame to close the openings at both ends of the frame. Then the two sleeves are immersed in deionized water at 37°C for 3 hours to dissolve at least a portion of the sodium chloride, thereby obtaining two sleeves with a hole structure, namely the first end cap and the second end cap. Further, the frame is heat-treated at 87°C for 9 minutes to shape the frame into a support frame including a first plugging unit, a second plugging unit and a waist. The average pore diameter of the holes of the first end cap and the second end cap are both 110 μm, and the porosity is both 18%.
[0139] The poly(L-lactic acid) particles were dissolved in a mixed solvent of 1,4-dioxane and deionized water to obtain a mixed solution, in which the volume ratio of 1,4-dioxane to deionized water was 95:5, and the mass of poly(L-lactic acid) accounted for 3% (mg / mL) of the volume of the mixed solvent. After the mixed solution was stirred at a constant temperature of 60°C for 3 hours, deionized water was added, and the volume of the added deionized water accounted for 15% of the volume of the mixed solution, and the mixture was stirred at a constant temperature of 60°C for 2 hours to obtain a mixture. The temperature of the mixture was kept at 60°C, and the support frame after plasma surface treatment was placed in the mixture. After soaking for 20 minutes, the support frame was vertically and slowly pulled out of the liquid surface, and slowly cooled to 2°C, kept for 60 minutes for roughening, and then transferred to liquid nitrogen at -196°C for cooling for 1 hour, and finally freeze-dried for 24 hours to form a poly(L-lactic acid) coating on the surface of the silk thread. The average pore size of the poly(L-lactic acid) coating was 200μm and the porosity was 20%.
[0140] Example 2
[0141] A group of 30 poly-L-lactic acid threads with a wire diameter of 0.10 mm and arranged in parallel and spaced apart are used as longitude threads and a group of 30 poly-L-lactic acid threads with a wire diameter of 0.10 mm and arranged in parallel and spaced apart are used as latitude threads. The longitude threads and latitude threads are cross-woven up and down to form a tubular structure with open ends. Two poly-L-lactic acid sleeves are used as the first and second heads to fix the threads at both ends of the frame to close the openings at both ends of the frame. Further, the frame is heat-treated at 87°C for 16 minutes to shape the frame into a support frame including a first plugging unit, a second plugging unit and a waist.
[0142] The poly(L-lactic acid) particles are dissolved in a mixed solvent of 1,4-dioxane and deionized water to obtain a mixed solution, wherein the volume ratio of 1,4-dioxane to deionized water is 80:20, and the mass of the poly(L-lactic acid) accounts for 8% (mg / mL) of the volume of the mixed solvent. After the mixed solution is stirred at a constant temperature of 60° C. for 8 hours, deionized water is added, and the volume of the added deionized water accounts for 2% of the volume of the mixed solution. The mixture is stirred at a constant temperature of 60° C. for 1 hour to obtain a mixture. The temperature of the mixture is maintained at 60°C, and the support frame, the first head and the second head after plasma surface treatment are placed in the mixture. After soaking for 20 minutes, the support frame is slowly pulled out of the liquid surface vertically and slowly cooled to 2°C. It is kept for 30 minutes for roughening, and then transferred to liquid nitrogen at -196°C for cooling for 2 hours, and finally freeze-dried for 24 hours to form a poly-L-lactic acid coating on the surface of the silk thread, the first head and the second head. The average pore size of the poly-L-lactic acid coating is 50 μm and the porosity is 85%.
[0143] Example 3
[0144] A group of 20 poly-L-lactic acid threads with a wire diameter of 0.40 mm and arranged in parallel and spaced apart are used as longitude threads and a group of 20 poly-L-lactic acid threads with a wire diameter of 0.40 mm and arranged in parallel and spaced apart are used as latitude threads. The longitude threads and latitude threads are cross-woven up and down to form a tubular structure with open ends. Two poly-L-lactic acid sleeves are used as the first and second heads to fix the threads at both ends of the frame to close the openings at both ends of the frame. Further, the frame is heat-treated at 93°C for 9 minutes to shape the frame into a blocking frame including a first blocking unit, a second blocking unit and a waist.
[0145] The poly(L-lactic acid) particles were dissolved in a mixed solvent of 1,4-dioxane and deionized water to obtain a mixed solution, in which the volume ratio of 1,4-dioxane to deionized water was 90:10, and the mass of poly(L-lactic acid) accounted for 6% (mg / mL) of the volume of the mixed solvent. After the mixed solution was stirred at a constant temperature of 60°C for 3 hours, deionized water was added, and the volume of the added deionized water accounted for 5% of the volume of the mixed solution, and the mixture was stirred at a constant temperature of 60°C for 2 hours to obtain a mixture. The temperature of the mixture was kept at 60°C, and the support frame, the first end cap and the second end cap were placed in the mixture. After soaking for 9 minutes, the support frame was slowly pulled out of the liquid surface vertically, and slowly cooled to 2°C, kept for 40 minutes for roughening, and then transferred to liquid nitrogen at -196°C for cooling for 1 hour, and finally freeze-dried for 24 hours to form a poly(L-lactic acid) coating on the surface of the silk thread, the first end cap and the second end cap. The average pore size of the poly(L-lactic acid) coating was 60μm and the porosity was 50%.
[0146] Example 4
[0147] A group of 20 poly(lactic acid) threads with a diameter of 0.40 mm and parallel spacing are used as longitude threads and a group of 20 poly(lactic acid) threads with a diameter of 0.40 mm and parallel spacing are used as latitude threads. The longitude threads and latitude threads are cross-woven up and down to form a tubular structure with open ends. After the poly(lactic acid) powder and sodium chloride (average particle size of 3 microns) are mixed uniformly at a mass ratio of 85:15, they are hot-melted at 90°C for 20 minutes, and a solid mixture is obtained after cooling. The solid mixture is processed into a sleeve, and the two sleeves are fixed to the threads at both ends of the frame to close the openings at both ends of the frame. Then the two sleeves are immersed in deionized water at 37°C for 2 hours to dissolve at least a portion of the sodium chloride, thereby obtaining two sleeves with a hole structure, namely the first end cap and the second end cap. Further, the frame is heat-treated at 90°C for 15 minutes to shape the frame into a support frame including a first plugging unit, a second plugging unit and a waist. The average pore diameter of the holes of the first end cap and the second end cap are both 5 μm, and the porosity is both 10%.
[0148] The poly(L-lactic acid) particles were dissolved in a mixed solvent of dichloromethane and deionized water to obtain a mixed solution, wherein the volume ratio of dichloromethane to deionized water was 90:10, and the mass of poly(L-lactic acid) accounted for 5% (mg / mL) of the volume of the mixed solvent. After the mixed solution was stirred at a constant temperature of 60°C for 3 hours, deionized water was added, and the volume of the added deionized water accounted for 5% of the volume of the mixed solution, and the mixture was stirred at a constant temperature of 60°C for 2 hours to obtain a mixture. The temperature of the mixture was kept at 60°C, and the support frame after plasma surface treatment was placed in the mixture. After soaking for 10 minutes, the support frame was vertically and slowly pulled out of the liquid surface, and slowly cooled to 2°C, kept for 1 minute for coarsening, and then transferred to liquid nitrogen at -196°C for cooling for 1 hour, and finally freeze-dried for 24 hours to form a poly(L-lactic acid) coating on the surface of the silk thread, and the average pore size of the poly(L-lactic acid) coating was 5μm and the porosity was 45%.
[0149] Example 5
[0150] A group of 20 poly-L-lactic acid threads with a wire diameter of 0.40 mm and arranged in parallel and spaced apart are used as longitude threads and a group of 20 poly-L-lactic acid threads with a wire diameter of 0.40 mm and arranged in parallel and spaced apart are used as latitude threads. The longitude threads and latitude threads are cross-woven up and down to form a tubular structure with open ends. After the poly-L-lactic acid powder and sodium chloride (average particle size of 80 microns) are mixed in a mass ratio of 50:50, they are heat-melted at 210°C for 15 minutes, and a solid mixture is obtained after cooling. The solid mixture is processed into a sleeve, and the two sleeves are fixed to the threads at both ends of the frame to close the openings at both ends of the frame. Then the two sleeves are immersed in deionized water at 37°C for 2 hours to dissolve at least a portion of the sodium chloride, thereby obtaining two sleeves with a hole structure, namely the first end cap and the second end cap. Further, the frame is heat-treated at 90°C for 13 minutes to shape the frame into a support frame including a first plugging unit, a second plugging unit and a waist. The first end cap and the second end cap have holes, and the porosity of the first end cap and the second end cap is 15%, the average pore diameter of the holes of the first end cap and the second end cap is 200 μm, and the porosity is 40%.
[0151] 2g of iohexol powder (average particle size 30μm) was dissolved in 50mL of methanol, and stirred thoroughly until clear to obtain a first solution. 4g of poly-L-lactic acid particles were dissolved in 100mL of chloroform to obtain a second solution. The first solution and the second solution were mixed and stirred at room temperature to obtain a mixture. The support frame was immersed in the mixture, and after 1 minute, it was slowly lifted out vertically, and vacuum dried at room temperature to form a poly-L-lactic acid film on the surface of the silk thread. After drying, the silk thread was immersed in water for 40 minutes to dissolve at least part of the iohexol in the poly-lactic acid film, and the average pore size of the porous poly-lactic acid coating was 40μm, and the porosity was 30%.
[0152] 10 g of iohexol powder was dissolved in 50 mL of methanol and stirred thoroughly until clarified to obtain a first solution. The support frame, the first head and the second head were immersed in the first solution for 20 minutes and then taken out. After drying, iohexol was deposited in the micropores of the polylactic acid coating and the holes of the first head and the second head, and iohexol was attached to the surface of the polylactic acid coating in the area without micropores.
[0153] Example 6
[0154] A group of 30 poly-L-lactic acid threads with a wire diameter of 0.20 mm and arranged in parallel and spaced apart are used as longitude threads and a group of 30 poly-L-lactic acid threads with a wire diameter of 0.30 mm and arranged in parallel and spaced apart are used as latitude threads. The longitude threads and latitude threads are cross-woven up and down to form a tubular structure with open ends. After the poly-racemic lactic acid powder and sodium chloride (average particle size of 60 microns) are mixed uniformly at a mass ratio of 85:15, they are hot-melted at 95°C for 15 minutes, and a solid mixture is obtained after cooling. The solid mixture is processed into a sleeve, and the two sleeves are fixed to the threads at both ends of the frame to close the openings at both ends of the frame. Then the two sleeves are immersed in deionized water at 37°C for 3 hours to dissolve at least a portion of the sodium chloride, thereby obtaining two sleeves with a hole structure, namely the first end cap and the second end cap. Further, the frame is heat-treated at 90°C for 15 minutes to shape the frame into a support frame including a first plugging unit, a second plugging unit and a waist.
[0155] 2 g of iohexol (50 μm) powder was dissolved in 50 mL of methanol and stirred until clear to obtain a first solution, 4 g of poly-L-lactic acid particles were dissolved in 100 mL of chloroform to obtain a second solution, the first solution and the second solution were mixed and stirred at room temperature to obtain a mixture. The support frame was immersed in the mixture, and after 1 minute, it was slowly lifted up vertically and vacuum dried at room temperature to form a poly-L-lactic acid coating on the surface of the silk thread, and the poly-L-lactic acid coating was filled with iohexol.
[0156] 10 g of iohexol powder was dissolved in 50 mL of methanol and stirred thoroughly until clarified to obtain a first solution. The support frame, the first head and the second head were immersed in the first solution for 30 minutes and then taken out. After drying, iohexol was deposited on the surface of the polylactic acid coating and in the holes of the first head and the second head.
[0157] Example 7
[0158] A group of 30 poly-L-lactic acid threads with a diameter of 0.20 mm and arranged in parallel and spaced apart are used as longitude threads, and a group of 30 poly-L-lactic acid threads with a diameter of 0.30 mm and arranged in parallel and spaced apart are used as latitude threads. The longitude threads and latitude threads are cross-woven up and down to form a tubular structure with open ends. The frame is heat-treated at 90° C. for 15 minutes to shape the frame into a tubular structure with open ends.
[0159] The poly(L-lactic acid) particles were dissolved in a mixed solvent of 1,4-dioxane and deionized water to obtain a mixed solution, in which the volume ratio of 1,4-dioxane to deionized water was 90:10, and the mass of poly(L-lactic acid) accounted for 5% (mg / mL) of the volume of the mixed solvent. After the mixed solution was stirred at a constant temperature of 60°C for 3 hours, deionized water was added, and the volume of the added deionized water accounted for 5% of the volume of the mixed solution, and the mixture was stirred at a constant temperature of 60°C for 2 hours to obtain a mixture. The temperature of the mixture was kept at 60°C, and the support frame after plasma surface treatment was placed in the mixture. After soaking for 10 minutes, the support frame was vertically and slowly pulled out of the liquid surface, and slowly cooled to 2°C, kept for 40 minutes for roughening, and then transferred to liquid nitrogen at -196°C for cooling for 1 hour, and finally freeze-dried for 24 hours to form a poly(L-lactic acid) coating on the surface of the silk thread, and a luminal stent with a poly(L-lactic acid) coating formed on the surface was prepared. The average pore size of the poly-L-lactic acid coating is 65 μm, and the porosity is 45%.
[0160] Comparative Example 1
[0161] The commercially available poly(lactic acid) threads are woven to form a frame, and the poly(lactic acid) threads do not have holes. A group of 20 poly(lactic acid) threads with a diameter of 0.40 mm, arranged in parallel and at intervals, are used as longitude threads and a group of 20 poly(lactic acid) threads with a diameter of 0.40 mm, arranged in parallel and at intervals, are used as latitude threads. The longitude threads and the latitude threads are woven up and down to form a tubular structure with open ends. Two poly(lactic acid) sleeves are used as the first and second heads to fix the threads at both ends of the frame to close the openings at both ends of the frame. The frame is heat treated at 87°C for 9 minutes to shape the frame into a closure frame including a first closure unit, a second closure unit and a waist, and an occluder is obtained.
[0162] The occluders of Example 1 and Comparative Example 1 were implanted in different Bama pigs, respectively. Two months after implantation, the occluder of Example 1 was completely endothelialized, while the occluding frame of the occluder of Comparative Example 1 was only partially covered by the endothelial cell membrane, while the first head and the second head were not yet covered by the endothelial cell membrane.
[0163] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0164] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An implantable device, comprising a support frame, characterized in that: The support frame comprises a plurality of mutually intersecting silk threads, the surface of the silk threads is provided with a polymer coating, the polymer coating has a plurality of micropores, the average pore size of the plurality of micropores is 5 μm to 500 μm, and the porosity of the polymer coating is 20% to 85%; The support frame includes a first plugging unit, a second plugging unit, a waist, a first head and a second head, the two ends of the waist are respectively connected to the first plugging unit and the second plugging unit, the first head is arranged at the end of the first plugging unit away from the waist, and the second head is arranged at the end of the second plugging unit away from the waist, and at least one of the first head and the second head has a hole; when the first head has a hole, the average pore size of the hole of the first head is 5μm~200μm, and the porosity is 10%~40%; when the second head has a hole, the average pore size of the hole of the second head is 5μm~200μm, and the porosity is 10%~40%.
2. The implantable device according to claim 1, characterized in that The support frame includes a first plugging unit, a second plugging unit, a waist, a first head and a second head, the two ends of the waist are respectively connected to the first plugging unit and the second plugging unit, the first head is arranged at the end of the first plugging unit away from the waist, and the second head is arranged at the end of the second plugging unit away from the waist, a polymer coating is arranged on the surface of one of the first head and the second head, the polymer coating has a plurality of micropores, the average pore size of the plurality of micropores is 5μm to 500μm, and the porosity of the polymer coating is 20% to 85%.
3. The implantable device according to claim 1, characterized in that When the first end cap has holes, the porosity is 30% to 40%; when the second end cap has holes, the porosity is 20% to 30%.
4. The implantable device according to claim 1, characterized in that The holes are filled with soluble substances.
5. A method for preparing an implantable device, characterized in that: The steps include: providing a support frame, the support frame comprising a plurality of mutually intersecting wires; dissolving a polymer in a first solvent to obtain a mixed solution, and adding a second solvent to the mixed solution to obtain a mixture; immersing the support frame in the mixture; After taking the support frame out of the mixture, cooling it to the gel point temperature of the polymer and roughening it at the gel point temperature; Cooling the roughened support frame, and then freeze-drying under vacuum to form a polymer coating on the multiple wires of the support frame, wherein the polymer coating has a plurality of micropores, the average pore size of the plurality of micropores is 5 μm to 500 μm, and the porosity of the polymer coating is 20% to 85%; The support frame includes a first head and a second head, at least one of the first head and the second head has a hole; when the first head has a hole, the average pore size of the hole of the first head is 5μm to 200μm, and the porosity is 10% to 40%; when the second head has a hole, the average pore size of the hole of the second head is 5μm to 200μm, and the porosity is 10% to 40%.
6. The method for preparing an implantable device according to claim 5, characterized in that: The volume of the second solvent accounts for 1-15% of the volume of the mixed solution, and the mass of the polymer accounts for 3%-30% of the volume of the first solvent, wherein the mass of the polymer is in milligrams and the volume of the first solvent is in milliliters.
7. The method for preparing an implantable device according to claim 5, characterized in that: In the step of immersing the support frame in the mixture, the immersion time is 1 to 20 minutes.
8. The method for preparing an implantable device according to claim 5, characterized in that: The roughening time is 1 to 60 minutes.
9. A method for preparing an implantable device, characterized in that: The steps include: providing a support frame, the support frame comprising a plurality of mutually intersecting wires; dissolving the polymer and the soluble substance in a first solvent to obtain a mixture; immersing the support frame in the mixture; removing the support frame from the mixture and drying it to form a polymer film on the surface of the filaments; The support frame is contacted with a second solvent, so that at least a portion of the soluble substance is dissolved while the polymer is not dissolved, thereby forming a polymer coating, wherein the polymer coating has a plurality of micropores, the average pore size of the plurality of micropores is 30 μm to 500 μm, and the porosity of the polymer coating is 20% to 85%; The support frame includes a first head and a second head, at least one of the first head and the second head has a hole; when the first head has a hole, the average pore size of the hole of the first head is 5μm to 200μm, and the porosity is 10% to 40%; when the second head has a hole, the average pore size of the hole of the second head is 5μm to 200μm, and the porosity is 10% to 40%.